Inhibiting Growth of Critical Thinking Skills (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
This manuscript will be addressing the need of developing critical thinking skills for students in social studies, specifically in the high school setting. The goal is for students to learn the material like historians would rather than through regurgitation of knowledge. To explore how to do so, this article explores methods in which to foster critical thinking skills. Such ways include the need for group-based assignments, different tactics of teaching vocabulary including with primary sources, and relating the material to students’ everyday experiences. Overall, these three things are imperative in improving a student’s capability of higher order/critical thinking and any methods addressed or not addressed that satisfy each category is for the benefit of critical thinking.